Identifying opportunities for enhancing collaboration in the Australian health insurance sector. (18th September 2006) - Daneshgar, Farhad; Bunker, Deborah; Lee, Kym Mawson
The Australian Health Insurance Sector (AHIS) is composed of multiple organisations with related but disparate e-business information systems. This paper introduces a process-based integrated conceptual model representing AHIS patients' claim processing. The aim of this representation is to facilitate identification of the awareness and knowledge-sharing requirements of the actors within the process; and as a result, to devise appropriate guidelines for enhacing collaboration among various actors. Through an awareness-provisioning methodology, the proposed process model will result in identification of the generic key e-business process integration issues related to the enhancement of collaboration within the AHIS. The syntactic, semantic and pragmatic qualities of the proposed conceptual model have been evaluated by presenting the results to experts within the AHIS and a general consensus has been arrived among them with regard to the model quality attributes. These results enabled AHIS experts in AHIS to devise domain-specific guidelines for removing the detected undesirable awareness gap. The proposed methodology can be replicated in similar situations.